Geo-spatial knowledge and intelligence. 5th International Conference, GSKI 2017, Chiang Mai, Thailand, December 8-10, 2017 : revised selected papers /: 5th International Conference, GSKI 2017, Chiang Mai, Thailand, December 8-10, 2017 : revised selected papers. Part I : ([2018]) - Unknown
No abstract available